(untitled) - Dower, J. W. (Cambridge, Mass., 1979)
This detailed biography of Japan's Postwar prime minister has had a favorable reception in the United States and has sold widely in translation in Japan.
Keywords: Yoshida, Shigeru,Prime ministers; Biography; Japan